Conduction mechanism via correlated barrier hopping in EC-plasticized 2-hydroxyehyl cellulose-ammonium nitrate solid polymer electrolyte - M I N Isa; M N Hafiza (IOP Publishing, 2024)
Volume 440, International Fundamentum Science Symposium 2018 25–26 June 2018, Terengganu, Malaysia